Sugar Palm Metabolism and Tolerance to Climate Change: A Little-Known Study of Physiology, Anatomy, and Biochemistry - Wisnubroto, Muhammad Parikesit; Cahyo, Andi Nur; Phuoc, Le Huu; Amin, Muhammad; Ernawati, Ernawati (AGRIVITA Journal of Agricultural Science, 2026)
Climate change is related to changes of climate patterns that impact unpredictable weather phenomena. These phenomena can include extreme heat, extremely low temperatures, drought, or extremely high rainfall. With high adaptability, sugar palm (Arenga pinnata Merr.) can be one of the conservative plants that have a vital role in mitigating global climate change. Sugar palms have a high ability of carbon dioxide (CO2) sequestration and store it in the form of biomass. The results of the review show that palm trees have an inherent tolerance mechanism, for example under dry conditions, sugar palm produces lignin to strengthen cell walls and increase antioxidant in the form of osmoprotectants. However, the lack of empirical data and detailed studies hinders a deeper understanding of the limits of this tolerance. This article highlights significant research gaps and recommends future studies to investigate in more detail gene-environment interactions, genetic adaptation potential, and the role of specific metabolites in sugar palm. Overall, sugar palm has a fairly high carbon absorption capacity of > 85 t/ha/year. Therefore, this article is expected to not only fill the knowledge gap but also serve as a foundation for conservation efforts and the sustainable use of sugar palm in facing global climate.